1978
DOI: 10.1093/clinchem/24.12.2151
|View full text |Cite
|
Sign up to set email alerts
|

Atomic absorption spectrophotometry of chromium in serum and urine with a modified Perkin-Elmer 603 atomic absorption spectrophotometer.

Abstract: Modification of a Perkin-Elmer 603 atomic absorption spectrophotometer by adding a high-intensity tungsten-halogen lamp for background correction significantly improved the detection limit for elements that have analytical wavelengths in the near-ultraviolet and visible regions. Chromium in human serum and urine can be measured, with a simplified sample-handling technique, in concentrations of less than 0.1 microgram/liter. For comparison, the mean value for chromium in the serum of eight men was 0.14 microgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Earlier it was believed that at least 10% of all Cr3+ ingested was absorbed (373,375,380), which, therefore, indicated that much Cr3+ in food existed as firm complexes. This conclusion was based on comparison of the above stated normal intake of Cr3+ and the normal urinary excretion, which was reported to be 5 to 10 ,ug/day (381,382). Recent determinations have, however, shown that the latter value is probably about 10 times in excess of the true value (383-391).…”
Section: Metabolism and Effects Of Similar Ionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Earlier it was believed that at least 10% of all Cr3+ ingested was absorbed (373,375,380), which, therefore, indicated that much Cr3+ in food existed as firm complexes. This conclusion was based on comparison of the above stated normal intake of Cr3+ and the normal urinary excretion, which was reported to be 5 to 10 ,ug/day (381,382). Recent determinations have, however, shown that the latter value is probably about 10 times in excess of the true value (383-391).…”
Section: Metabolism and Effects Of Similar Ionsmentioning
confidence: 96%
“…The remainder is ultraffiltrable and very likely bound to various complexforming small molecules. Information reFarding the normal concentration in serum, as with Al +, is contradictory (366,395-397), but recent values of about 0.15 ,ug/ L are most plausible (381,395). In that case, the concentration corresponds to 2 to 3% of the supposed molar concentration of A13+.…”
Section: Metabolism and Effects Of Similar Ionsmentioning
confidence: 99%
“…Lead, Arsenic, Mercury, and Selenium were estimated using atomic absorption spectrometer (AAS) with samples digestion done according to the method described by Kayne et al [22]. More so, the concentration of testosterone and glutathione peroxidase enzyme in the seminal plasma was determined using ELISA technique as described in the work done by Adele et al [23].…”
Section: Evaluation Of Biochemical Parameters In Seminal Plasmamentioning
confidence: 99%
“…1 mg/ ml) at 37°C. For incubations of isolated fat cells the medium described in Gliemann (1965) was used containing 50 nCi D-[1-14 C]glucose, final concentration 0.11 mg/ml. Reaction was stopped by addition of 0.5 ml H 2 SO 4 4 mol/l, and C0 2 was trapped according to Gliemann (1965) and counted in a Packard Tri-Carb liquid scintillation spectrometer.…”
Section: Isolation Of Fat Tissuesmentioning
confidence: 99%
“…Chromium was determined on a 240 mark 2 atomic absorption spectrophotometer (Evans electroselenium LTP, Halsted, England) with a hollow cathode lamp with an absorption optimum at 357.8 nm. Digestion was performed in a 1:1 mixture of nitric acid and hydrogen peroxide (Kayne, Komar, Laboda and Vauderlinde 1978) for 16 hours at 96°C. K,Cr,0, was used as a standard.…”
Section: Determination Of Chromiummentioning
confidence: 99%